2016
DOI: 10.1039/c5nr07490h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical self-assembly of switchable nucleolipid supramolecular gels based on environmentally-sensitive fluorescent nucleoside analogs

Abstract: Exquisite recognition and folding properties have rendered nucleic acids as useful supramolecular synthons for the construction of programmable architectures. Despite their proven applications in nanotechnology, scalability and fabrication of nucleic acid nanostructures still remain a challenge. Here, we describe a novel design strategy to construct new supramolecular nucleolipid synthons by using environmentally-sensitive fluorescent nucleoside analogs, based on 5-(benzofuran-2-yl)uracil and 5-(benzo[b]thioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 91 publications
0
40
0
Order By: Relevance
“…S1, ESI †) were synthesised and used to prepare gel films on piranha cleaned silicon wafers (OH surfaces). This family of gelators was selected over other nucleolipid-based gelators under investigations 14,[18][19][20] as they are synthesized through a straightforward, one-pot synthetic route, 21 their mechanism of self-assembly is well-understood 17 and they have shown promising potential in drug delivery applications. 21 The OH surfaces (surfaces covered with hydrophilic hydroxyl groups) were characterized with AFM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1, ESI †) were synthesised and used to prepare gel films on piranha cleaned silicon wafers (OH surfaces). This family of gelators was selected over other nucleolipid-based gelators under investigations 14,[18][19][20] as they are synthesized through a straightforward, one-pot synthetic route, 21 their mechanism of self-assembly is well-understood 17 and they have shown promising potential in drug delivery applications. 21 The OH surfaces (surfaces covered with hydrophilic hydroxyl groups) were characterized with AFM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…as key driving forces in self-assembly. [12][13][14][15][16][17] Previously, we have shown that an alkyl-modified derivative of cytidine produces gel films with different mechanical properties on a hydrophilic and a hydrophobic surface. 11 AFM measurements showed that the dried gels displayed fibres with larger diameters on the hydrophobic than on the hydrophilic surface.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Sonotropy has been much less investigated. 15,51,52 However, both abilities were recently reported for ILGs. 29,31,32,34 Our data are displayed in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The same approach was used very recently to provide NL hybrids incorporating emissive nucleosides following very classical coupling reaction conditions with a variety of lipidic chains before the Stille reaction step ( Figure A) . Fluorescent derivatives were shown to exhibit a good gelation ability in organic solvents.…”
Section: Nucleolipidsmentioning
confidence: 98%
“…B) Gel images under UV light (top, 365 nm) and gelation properties of fluorescent NLs (bottom). Reproduced with permission . Copyright 2016, Royal Society of Chemistry.…”
Section: Nucleolipidsmentioning
confidence: 99%